Spiral-shaped scattered field from incident evanescent acoustic waves on a Mie Particle. Issue 1 (January 2021) - Alhaïtz, Ludovic; Baresch, Diego; Brunet, Thomas; Aristégui, Christophe; Poncelet, Olivier
Abstract: We consider theoretically the scattering of an incident evanescent plane wave by a spherical particle. The scattering problem is treated in a classic way by applying the T-matrix formalism and the resulting field is expressed on the basis of the different vibration modes of the particle. Compared to the case of a homogeneous plane incident wave, additional azimuthal scattered modes are excited and their contribution provokes a symmetry breaking of the field. Importantly, if a mode is preferentially excited by choosing the corresponding reduced frequency, the scattered radiation exhibits a spiral structure. The scattered field has a rotating phase around the scatterer which comes from the formation of spiral scattered waves and this effect is accentuated by increasing the evanescence degree of the incident wave. These results could have important implications for the contactless manipulation of objects with acoustic radiation forces and torques.